Climate-driven changes in air quality over Europe by the end of the 21st century, with special reference to Portugal - Carvalho, A. (2010)
Climate change alone may deeply impact air quality levels in the atmosphere because the changes in the meteorological conditions will induce changes on the transport, dispersion and transformation of air pollutants. The aim of this work was to evaluate the impact of climate change on the air quality over Europe and Portugal, using a reference year (year 1990) and a IPCC SRES A2 year (year 2100). The Hadley Centre global atmospheric circulation model (HadAM3P) was used to provide results for these two climatic scenarios, which were then used as synoptic forcing for the MM5-CHIMERE air quality modelling system. In order to assess the contribution of future climate change on 03 and PM concentrations, no changes in regional emissions were assumed and only climate change forcing was considered. The modelling results suggest that the O(3) monthly mean levels in the atmosphere may increase almost 50 mu g m(-3) across Europe in July under the IPCC SRES A2 scenario. In Portugal, this increase may reach 20 mu g m(-3). The changes of PM10 monthly average values over Europe will depend on the region. The increase in PM10 concentrations during specific months could be explained by the average reduction of the boundary layer height and wind speed. (C) 2010 Elsevier Ltd. All rights reserved.